Atmospheric pressure cold plasma (ACP) treatment of whey protein isolate model solution. (May 2015) - Segat, Annalisa; Misra, N.N.; Cullen, P.J.; Innocente, Nadia
Abstract: The interaction between atmospheric pressure cold plasma (ACP) and whey protein isolate (WPI) model solutions was investigated as a function of treatment time (from 1 to 60 min). The results showed an increase in yellow colour and a minor reduction in pH value, which was attributed to the reactions of reactive oxygen and nitrogen species of the plasma. Following ACP treatments for 15 min, mild oxidation occurred in the proteins. This was evident from an increase in carbonyl groups and the surface hydrophobicity, besides the reduction of free SH groups. The protein structure modifications revealed a certain degree of unfolding, as confirmed by dynamic light scattering (DLS) and high performance liquid chromatography (HPLC) profiles, which improve foaming and emulsifying capacity. Upon extended treatment for 30 and 60 min, the changes were quite pronounced. Overall, the foaming and emulsifying capacity dramatically decreased; nevertheless the foam stability increased. Industrial relevance: Among emerging non-thermal technologies, atmospheric pressure cold plasma (ACP) has gained enormous pace especially for its safety assurance and sustainability. Many studies and data regarding ACP inactivation of food-borne pathogens are already available in the literature. Most of them concern the decontamination by microorganisms in buffer or food matrices. However, ACP provides opportunities in several other applications. To this regard, the effects between ACP generated by a dielectric barrier discharge using air as gas and whey protein isolate (WPI) model solutions were evaluated. This study demonstrated that ACP can be successfully applied in order to selectively modify the protein structure and therefore, improve WPI functionality. This allows to use ACP-treated WPI as ingredient in different formulated food to express targeted functionality. Highlights: The ACP (atmospheric pressure cold plasma) treatments for 15 min generated mild oxidation in the whey proteins An increase of yellow colour in the solutions and a slight decrease of pH were observed The protein structure modifications revealed a certain degree of unfolding Improvement of foaming and emulsifying capacities Upon extended treatment for 30 and 60 min the foam stability increased